2021
DOI: 10.3389/fneur.2021.662839
|View full text |Cite
|
Sign up to set email alerts
|

Wavelet Autoregulation Monitoring Identifies Blood Pressures Associated With Brain Injury in Neonatal Hypoxic-Ischemic Encephalopathy

Abstract: Dysfunctional cerebrovascular autoregulation may contribute to neurologic injury in neonatal hypoxic-ischemic encephalopathy (HIE). Identifying the optimal mean arterial blood pressure (MAPopt) that best supports autoregulation could help identify hemodynamic goals that support neurologic recovery. In neonates who received therapeutic hypothermia for HIE, we hypothesized that the wavelet hemoglobin volume index (wHVx) would identify MAPopt and that blood pressures closer to MAPopt would be associated with less… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…Multiple studies in term infants with moderate-severe HIE have reported impaired cerebral autoregulation during and after therapeutic hypothermia ( 55 , 56 ). Recent studies have refined time and frequency domain analysis of NIRS parameters to quantify autoregulatory disturbances, such as spectral coherence analysis of mean arterial pressure (MAP) and NIRS parameters (hemoglobin difference) to calculate pressure passivity, moving correlation coefficient between MAP and relative total tissue hemoglobin concentration to calculate time spent below optimal MAP (range of MAP with the most dynamic vascular reactivity), and wavelet-coherence analysis of MAP and cerebral oxygen saturation ( 55 , 57 , 58 ). These studies showed that the extent of autoregulatory disturbances during hypothermia and rewarming are associated with injury severity and adverse neurodevelopmental outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Multiple studies in term infants with moderate-severe HIE have reported impaired cerebral autoregulation during and after therapeutic hypothermia ( 55 , 56 ). Recent studies have refined time and frequency domain analysis of NIRS parameters to quantify autoregulatory disturbances, such as spectral coherence analysis of mean arterial pressure (MAP) and NIRS parameters (hemoglobin difference) to calculate pressure passivity, moving correlation coefficient between MAP and relative total tissue hemoglobin concentration to calculate time spent below optimal MAP (range of MAP with the most dynamic vascular reactivity), and wavelet-coherence analysis of MAP and cerebral oxygen saturation ( 55 , 57 , 58 ). These studies showed that the extent of autoregulatory disturbances during hypothermia and rewarming are associated with injury severity and adverse neurodevelopmental outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Continuous NIRS blood pressure autoregulation monitoring after neonatal HIE can identify neonates at greatest risk of brain injury or death. Despite years of neonatal au-toregulation research [6,8,10,14,30,[33][34][35], an optimal autoregulation index has not been integrated into clinical practice. We undertook the current study to examine three candidate autoregulation indices that have shown promise in preclinical [15] and single-center clinical [7][8][9][10][11]36] HIE studies.…”
Section: Discussionmentioning
confidence: 99%
“…Since all our autoregulation indices become positive when blood pressure is below or above the limits of autoregulation, we cannot conclude whether the link between dysfunctional autoregulation and poor outcome were weighted towards hypo- or hypertension. However, prior research indicates that blood pressure below the optimal autoregulatory range is the larger contributor to brain injury [8-11, 14, 36]. While prior approaches have focused on identifying the optimal MAP with most robust autoregulation, optimal MAP cannot be identified in all neonates [11].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Table 3 summarizes all multicentre studies and surveys that describe the types of sedation/analgesia practices [34,[48][49][50][51][52][53]. Seven studies mentioned using "routine" sedation for all neonates undergoing TH [29,37,[54][55][56][57][58]. Gagne-Loranger et al reported the results from a prospective study (2008-2012) in which neonates were not regularly sedated during TH but received boluses of morphine only if they were uncomfortable [59].…”
Section: Prospective Cohort Study N = 44 Questionmentioning
confidence: 99%